Gusti Yesus Rawuh Paring Urip Lan Kaluberan: (Pengabdian Melalui Pembinaan Iman Dalam Rangka Paskah di G.Pibi Amanat Agung, Pos Pelayanan Mojo Gedang, Karang Anyar, Jawa Tengah) - Epafras Mujono; Ruth Melisa (Nusantara Mengabdi Kepada Negeri, 2024)
The background to this Community Service Activity (PkM) is: First, there is a need among congregation members for speakers/lecturers/who can speak Javanese so that the participants better understand the material for faith formation, in the context of commemorating Good Friday and Easter. Second, there is a need to refresh the commitment of congregation members in their faith in Jesus Christ. Third, there is a need for a correct understanding of Good Friday and Easter for the general public, so that they get the correct information about this. The aim of this Community Service activity is as follows: First, so that the message of the lecture about the coming of Jesus who gives life and abundance (John 10:10b) can be captured or understood more clearly by the recipients of this PkM service, because it is delivered in Javanese . Second, to explain the material for community service through faith formation lectures. Third, to determine respondents' satisfaction as participants in this community service activity. The results of this devotion are: First, faith formation material with the theme "Christ came to give life and abundance" including that Jesus is the door to guaranteeing safety and security, Jesus came to give life and abundance and Jesus guides the lost sheep. The level of satisfaction of the participants with the material and its delivery is at the level of hight (85,11%).